Aspects of human physical and behavioural evolution during the last 1 million years. (14th August 2019) - Galway‐Witham, Julia; Cole, James; Stringer, Chris
ABSTRACT: This paper reviews some of the main advances in our understanding of human evolution over the last 1 million years, presenting a holistic overview of a field defined by interdisciplinary approaches to studying the origins of our species. We begin by briefly summarizing the climatic context across the Old World for the last 1 million years before directly addressing the fossil and archaeological records. The main themes in this work explore (i) recent discoveries in the fossil record over the last 15 years, such as Homo naledi and Homo floresiensis ; (ii) the implications of palaeogenetics for understanding the evolutionary history of, and relationships between, Neanderthals, Denisovans and Homo sapiens ; (iii) the interplay between physiology and metabolic demand, landscape use, and behavioural adaptations in the evolution of morphological and behavioural innovation; and (iv) recent advances in archaeological understanding for the behavioural record, in particular that of the Neanderthals. This paper seeks to provide a broad‐scale, holistic perspective of our current understanding of human evolution for the last 1 Ma, providing a reference point for researchers that can be built upon as new discoveries continue to develop the landscapes of human evolution. © 2019 The Authors. Journal of Quaternary Science Published by Wiley Periodicals, Inc.